2014
DOI: 10.1177/0145721714535994
|View full text |Cite
|
Sign up to set email alerts
|

“We Are All Gonna Get Diabetic These Days”

Abstract: Purpose The purpose of this study was to investigate how an intergenerational legacy of type 2 diabetes affected the knowledge, attitudes, and treatment strategies of Hispanic young adults with diabetes. Methods Eight Hispanic young adults (ages 18-30 years) participated in a series of in-home longitudinal qualitative interviews, and 11 of their family members completed single in-home interviews, regarding their diabetes management practices. Interview transcripts were analyzed thematically by a team of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Most studies were excluded because none relevant outcomes were reported ( n =453), and/or type of care was not integrated ( n =257). After the title, abstract and full text screening, 27 studies were included (Groeneveld et al ., 2001; Ostgren et al ., 2002; El-Kebbi et al ., 2003; Rothman et al ., 2003; Rothman et al ., 2004; Uitewaal et al ., 2004; Benoit et al ., 2005; Sperl-Hillen and O’Connor, 2005; Uitewaal et al ., 2005; De Alba Garcia et al ., 2006; Nielsen et al ., 2006; Taweepolcharoen et al ., 2006; Trief et al ., 2006; Wahba and Chang, 2007; Mold et al ., 2008; Al Omari et al ., 2009; De Fine Olivarius et al ., 2009; Robinson et al ., 2009; Kellow et al ., 2011; Cardenas-Valladolid et al ., 2012; Elissen et al ., 2012; Liu et al ., 2013; Quah et al ., 2013; LeBlanc et al ., 2015; Luijks et al ., 2015; Moreira et al ., 2015; Quinn et al ., 2016).
Figure 1Flow diagram of the study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were excluded because none relevant outcomes were reported ( n =453), and/or type of care was not integrated ( n =257). After the title, abstract and full text screening, 27 studies were included (Groeneveld et al ., 2001; Ostgren et al ., 2002; El-Kebbi et al ., 2003; Rothman et al ., 2003; Rothman et al ., 2004; Uitewaal et al ., 2004; Benoit et al ., 2005; Sperl-Hillen and O’Connor, 2005; Uitewaal et al ., 2005; De Alba Garcia et al ., 2006; Nielsen et al ., 2006; Taweepolcharoen et al ., 2006; Trief et al ., 2006; Wahba and Chang, 2007; Mold et al ., 2008; Al Omari et al ., 2009; De Fine Olivarius et al ., 2009; Robinson et al ., 2009; Kellow et al ., 2011; Cardenas-Valladolid et al ., 2012; Elissen et al ., 2012; Liu et al ., 2013; Quah et al ., 2013; LeBlanc et al ., 2015; Luijks et al ., 2015; Moreira et al ., 2015; Quinn et al ., 2016).
Figure 1Flow diagram of the study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…A sense of inevitability about developing diabetes is prevalent among other marginalized populations, including American Indians, 4850 African Americans, 51,52 and Hispanics. 53,54 The perception that diabetes is inevitable is influenced in part by family history and the belief that diabetes is hereditary, 49–51 as well as fatalistic beliefs that diabetes is beyond one's control and may be the will of God, nature, or the universe. 48,53 It is imperative to navigate ways to increase self-efficacy while respecting culturally-based fatalistic beliefs regarding developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This definition was later expanded to include the following: (1) the participant qualified for income-restricted government entitlement programs (e.g., MediCal/Medicaid, Supplemental Nutrition Assistance Program); (2) the participant had a household income of 250% of Federal Poverty Level or lower; or (3) neither of the participant’s parents had attained a four-year college degree. Participants were excluded if they had cognitive disabilities or severe impairments that limited life expectancy; were pregnant or planned a pregnancy within the next 6 months; had participated in a diabetes management intervention beyond diabetes education offered in usual clinic visits totaling ≥6 hours within the past year; or if they had participated in qualitative research used to inform the development of the REAL Diabetes intervention (23, 24). …”
Section: Methodsmentioning
confidence: 99%
“…The Lifestyle Redesign intervention framework has been shown in two large-scale randomized controlled trials (RCTs) to cost-effectively improve physical and mental well-being, and facilitate maintenance of therapeutic gains over the long term (17, 18, 21, 22). To adapt this framework to address the needs of the targeted population, our research team conducted a qualitative needs assessment amongst young adults with both T1D and T2D (23, 24), and developed and validated an intervention manual among a small sample of young adults with diabetes (25). After completing intervention development and validation, our research team initiated a pilot RCT, described herein, to evaluate the efficacy of the intervention and further optimize its implementation in preparation for a large-scale RCT.…”
Section: Introductionmentioning
confidence: 99%